Chile : Financial Sector Assessment Program-Technical Note on Crisis Management and Bank Resolution. (IMF Staff Country Reports; Country Report, 2022)
Chile has a large and well-developed financial system, compared with the rest of Latin America. The market is well integrated into the global financial system, with Chilean firms investing in foreign financial assets, either directly or via institutional investors, and foreigners participating in the Chilean market.